Pengaruh Kualitas Pelayanan, Citra Toko Dan Store Atmosphere Terhadap Kepuasan Konsumen (Studi Kasus Pada Toko Sumber Agung Pasuruan) - Ferdiansyah, Muhammad Agung; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze and assess the influence of Service Quality (X1), Store Image (X2), and Store Atmosphere (X3) on Consumer Satisfaction, both partially and simultaneously. The research method applied is a quantitative approach. The sample for this research was 60 consumers of the Sumber Agung Pasuruan Store. The questionnaire was used as a data collection instrument, Validity Test and Reliability Test were used to measure the performance of the instrument. Not only that, this research also used Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis, F Test, R2 Test, and t Test. The results of this research show that Service Quality, Store Image, and Store Atmosphere. Simultaneously has a positive and significant effect on Consumer Satisfaction. Partially, Service Quality, Store Image and Store Atmosphere have a positive and significant effect on Consumer Satisfaction. Keywords: Service Quality, Store Image, Store Atmosphere and Consumer Satisfaction